2019
DOI: 10.1055/s-0039-1693527
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Distilled Liquid Smoke Derived from Coconut (Cocos nucifera L) Shell for Traumatic Ulcer Healing in Diabetic Rats

Abstract: Objective Distilled liquid smoke (DLS) is a result of coconut processing by-product that not only serves as a natural food preservative but also has a promising therapeutic effect. The healing potential of DLS derived from coconut (Cocos nucifera L) shell was investigated on a traumatic ulcer with the diabetic rat. Materials and Methods DLS was analyzed the component by gas chromatograph mass spectrometry. Diabetic condition was induced by alloxan in 55 male Wistar rats. Ten mm of traumatic ulcer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 36 publications
(48 reference statements)
0
63
2
1
Order By: Relevance
“…The main phenolic compounds in LC-SS are phenol, guaiacol, and 4-ethly-2-methoxyphenol. 16 Phenolic compound has a hydroxyl group (-OH) that is directly bound to an aromatic hydrocarbon ring. 19 Previous research has shown that topical treatment of LC-SS promotes oral ulcer healing, 15 by increasing the production of collagens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main phenolic compounds in LC-SS are phenol, guaiacol, and 4-ethly-2-methoxyphenol. 16 Phenolic compound has a hydroxyl group (-OH) that is directly bound to an aromatic hydrocarbon ring. 19 Previous research has shown that topical treatment of LC-SS promotes oral ulcer healing, 15 by increasing the production of collagens.…”
Section: Discussionmentioning
confidence: 99%
“…A pyrolysis process was conducted at 400°C prior to distillation at 120 to 150°C to produce distilled liquid smoke. 15,16…”
Section: Distilled Liquid Smoke Productionmentioning
confidence: 99%
“…9,24 The application of LS-CE may affect the regulatory macrophages. The phenolic compounds in the LS-CE are able to decrease the M2 macrophages to produce the proinflammatory cytokine like TNF-α, 14 by inhibiting the activation of NF-kB. 14 Meanwhile, in the wound-healing process, lymphocytes have a modulatory role.…”
Section: Ls-ce Role In Fibroblasts Ernawati Et Almentioning
confidence: 99%
“…The NF-κB pathway has been considered as the prototypical pro-inflammatory signaling pathway largely based on the activation of NF-κB by pro-inflammatory cytokines such as TNF-α. 7 TNF-α can induce the degradation of NF-κB inhibitor (IκB) via a specific cascade pathway. IκB sequesters NF-κB in the cytoplasmic compartment by binding to its inhibitory subunit.…”
Section: Discussionmentioning
confidence: 99%
“…6 The TNF-α is a pro-inflammatory cytokine produced by activating the NF-κB. 7 The inhibition of NF-κB and TNF-α is the key for the anti-inflammatory effect to increase the oral mucosal wound healing. 8 This study was therefore designed to evaluate the anti-inflammatory effect of Musa acuminata through expression of TNF-α and NF-κB after 3 days of application of MASE on oral mucosal wounds.…”
Section: Introductionmentioning
confidence: 99%